The luge start: Rotator cuff and scapulothoracic stabilization exercises to consider - Cerullo, J. (Strength and Conditioning Journal, 2011)
The luge start imposes a significant stress on the upper and lower back. Muscle strains were the second leading cause of injuries experienced by luge athletes during 1985-1992, accounting for 27% of all injuries. When classified in relation to body location, the top 4 consisted of the neck, hand, back, and shoulder. Although world-class luge athletes train year round, research specific to the sport is scarce. The purpose of this article is to present some common shoulder rehabilitation exercises to consider when training to promote efficient movement of the shoulder girdle complex during the luge start.